A simple, safe and sensitive method for SARS-CoV-2 inactivation and RNA extraction for RT-qPCR - Kalnina, L; Mateu-Regué, À; Oerum, S; Hald, A; Gerstoft, J; Oerum, H; Nielsen, FC; Iversen, AKN (Wiley, 2021)
The SARS‐CoV‐2 pandemic has created an urgent need for diagnostic tests to detect viral RNA. Commercial RNA extraction kits are often expensive, in limited supply, and do not always fully inactivate the virus. Together, this calls for the development of safer methods for SARS‐CoV‐2 extraction that utilize readily available reagents and equipment present in most standard laboratories. We optimized and simplified a RNA extraction method combining a high molar acidic guanidinium isothiocyanate (GITC) solution, phenol and chloroform. First, we determined the GITC/RNA dilution thresholds compatible with an efficient two‐step RT‐qPCR for B2M mRNA in nasopharyngeal (NP) or oropharyngeal (OP) swab samples. Second, we optimized a one‐step RT‐qPCR against SARS‐CoV‐2 using NP and OP samples. We furthermore tested a SARS‐CoV‐2 dilution series to determine the detection threshold. The method enables downstream detection of SARS‐CoV‐2 by RT‐qPCR with high sensitivity (~4 viral RNA copies per RT‐qPCR). The protocol is simple, safe, and expands analysis capacity as the inactivated samples can be used in RT‐qPCR detection tests at laboratories not otherwise classified for viral work. The method takes about 30 min from swab to PCR‐ready viral RNA and circumvents the need for commercial RNA purification kits.